Latitudinal distribution of extant fossilizable phytoplankton in the Southern Ocean: Planktonic provinces, hydrographic fronts and palaeoecological perspectives - MALINVERNO, ELISA; MAFFIOLI, PAOLA; Gariboldi, K. (Marine Micropaleontology, 2016)
We present the combined abundance of all extant fossilizable planktonic groups (Dinoflagellates, Coccolithophores, Silicoflagellates, Diatoms, Parmales, Archaeomonads and micro-zooplankton) from surface waters collected along a latitudinal transect in the western Pacific sector of the Southern Ocean, ranging from ∼ 48°S, offshore New Zealand, to ∼ 70°S in the Ross Sea, Antarctica. Latitudinal shifts in species' distribution correspond with the Antarctic Circumpolar Current fronts and with the seasonal position of the ice-edge. Distinct bioprovinces are defined by clustering samples with a high degree of similarity. Our data confirm the importance of previously-defined taxa as palaeoceanographic proxies but also reveal some differences: the shift in dominance between the silicoflagellates genera Dictyocha and Stephanocha, used as a proxy of palaeo sea-surface temperatures, occurs slightly north of the Southern Sub-Antarctic Front rather than at the Polar Front; the shifts in abundance between the open-ocean diatom species Fragilariopsis kerguelensis and sea-ice related F. curta and F. cylindrus, as well as the drop in the coccolithophore Emiliania huxleyi, occur at the southern Antarctic Circumpolar Front rather than at the Polar Front. Finally, we introduce the Corona-index, based on the ratio of the coronatid to non-coronatid silicoflagellates species Stephanocha speculum, as a new proxy for sea-ice and we confirm the occurrence of abundant Archaeomonads and Parmales (Triparma laevis subsp. ramispina) in the marginal ice-edge zone.